[PP.28.27] IS THAT OBSTRUCTIVE SLEEP APNEA PARTICIPATES IN THE DECREASE OF THE ANTIAGGREGANT EFFECT OF THE ASPIRIN OBSERVED IN PATIENTS WITH DIABETES MELLITUS. (September 2017) - Ormezzano, O.; Borel, A.L.; Tamisier, R.; Marlu, R.; Faure, P.; Polack, B.; Benhamou, P.Y.; Pépin, J.L.
Abstract : Objective: Asprin resistance is more frequent in diabetes and is associated with a poor health outcome. Intermitent hypoxemia in patient with obstructive sleep apnea (OSA) is associated with platelet activation. OSA is frequent in patient with diabetes mellitus. The aim of this study was to investigate the role of the OSA in aspirin resistance in diabetes. Design and method: Patients with diabetes mellitus, taking aspirin for primary prevention or stable atherothrombotic disease, underwent overnight, in-lab polysomnography. The following morning we used the VerifyNow aspirin system to evaluate the efficacy of aspirin. Patients with at least an apnea-hypopnea index of 30 events/hours were diagnosed with severe OSA. Results: The preliminary result of the fifty first consecutive patients included in the study is presented: Figure. No caption available. Conclusions: In these preliminary results, the OSA seems not be influence the aspirin response in patients with diabetes.